Case report: Kikuchi-Fujimoto disease: unveiling a case of recurrent fever and enlarged cervical lymph nodes in a young female patient with a literature review of the immune mechanism - Yu, Jia-Li; Li, Zhen; Zhang, Bo; Huang, Ya-Nan; Zhao, Tian-Yu (Frontiers in Immunology, 2024)
The inflammatory response to viral infection is an important component of the antiviral response, a process that involves the activation and proliferation of CD8+ T cells, CD4+ T cells, and dendritic cells; thus, viral infection disrupts the immune homeostasis of the organism, leading to an increased release of inflammatory factors. Kikuchi-Fujimoto disease (KFD) is an inflammatory self-limited disorder of unknown etiology, which is generally believed that the pathogenesis of this disease included two aspects: viral infection and autoimmune response. Various immune cells such as CD8+ T lymphocytes, CD4+ T lymphocytes, and CD123+ plasmacytoid dendritic cells, as well as the cytokines they induce and secrete, such as interferons, interleukins, and tumor necrosis factors, play a crucial role in the pathogenesis of KFD. In this paper, we present a case study of a young female patient from China who exhibited typical symptoms of lymph node inflammation and fever. The diagnosis of KFD was confirmed through a lymph node biopsy. She presented with elevated ESR, IL-6 and IFN-γ. Viral markers showed elevated IgG and IgM of cytomegalovirus (CMV) and elevated IgG of Epstein Barr Virus (EBV), while changes happened in the counts of CD4+ T cell and CD8+ T cell. Eventually, the patient achieved disease relief through steroid treatment. Based on these findings, we conducted a comprehensive review of the involvement of viral infection-induced inflammatory response processes and autoimmunity in the pathogenesis of Kikuchi-Fujimoto Disease.